ANALYSIS OF INTEREST RATE. INFLATION RATE, AND EXCHANGE RATE ON STOCK PRICE VOLATILITY AND TRADING VOLUME: EVIDENCE FROM INDONESIA STOCK EXCHANGE - Asali, Miriam (Jurnal Manajemen Update, 2019)
ABSTRACTThe capital market plays an important role in the economic development of a country. One of the main factors that motivate investors to invest their fund in the capital market is because of the expectation of a return. Besides expecting returns, investors should bear the risk of investment. Volatility can represent the risk that may be faced by the investor when conduct stock trading activity. Investors will look to the stock price volatility in determining the risk and opportunity of stock trading. Besides the volatility of stocks, trading volume is one indicator that can be used by the investors in analyzing the overall performance of the stocks. Fluctuation in the stock price is mostly related to the change in macroeconomic factors in a country. It is important for the investor to figure out how the macroeconomic variables affect the stock market to pick out the best-fit investment. Hence, this study is aimed to analyze the impact of macroeconomic variables on stock price volatility and trading volume.The sample in this study is monthly data listed in Indonesia Stock Exchange in the period of 2008 to 2018. The number of observation in this study is 132. The macroeconomic variables are measured by interest rate, inflation, and exchange rate. The data are analyzed using GARCH Model. The model selection is based on the value of R2, AIC and SC.The results show that only inflation has a significant influence on stock price volatility in Indonesia Stock Exchange. Inflation has a negative and significant relationship with stock price volatility. Other variables such as interest rate and exchange rate have an insignificant influence on stock price volatility. On the other hand, interest rate, inflation, and exchange rate have no significant influence on trading volume. Â Keywords: Stock Price Volatility, Trading Volume, Interest Rate, Inflation, Exchange RateREFERENCESAdjasi, C. K. (2009). Maccroeconomic Uncertainty and Conditional Stock-price Volatility in Frontier African Markets Evidence from Ghana. The Journal of Risk Finance, 10(4).Agung, I. G. (2009). Time Series Data Analysis Using Eviews. Singapore: John Wiley & Sons (Asia) Pte Ltd.Amata, E. O. (2017). Effect of Macroeconomic Variables on Stock Market Volatility in kenya (Unpublished Doctoral Thesis), Jomo Kenyatta University of Agriculture and Technology, Kenya.Andiani, N. W., & Gayatri. (2018). Pengaruh Volume Perdagangan Saham, Volatilitas Laba, Dividend Yield, dan Ukuran Perusahaan Pada Volatilitas Harga Saham. E-Jurnal Akuntansi Universitas Udayana, 24(3).Asteriou, D., & Hall, S. G. (2007). Applied Econometrics A Modern Approach . New York: PALGRAVE MACMILLAN.Azis, M., Mintarti, S., & Nadir, M. (2015). Manjemen Investasi Fundamental, Teknikal, Perilaku Investor dan Return. Yogyakarta: Deepublish.Chan, K., & Fong, W.-M. (2000). Trade size, order imbalance, and the volatility-volume relation. Journal of Financial Economics 57, 247-273.Chinzara, Z. (2010). Macroeconomic uncertainty and emerging market stock market volatility: The case for South Africa. Rhodes University, Working Paper 187.Creswell, J. W. (2003). Research Design Qualitative, Quantitative, and Mixed Methods Approach. United States: Sage Publications.Dewi, N. M., & Suaryana, I. G. (2016). Pengaruh Volume Perdagangan Saham, Leverage, dan Tingkat Suku Bunga Terhadap Volatilitas Harga Saham. E-Jurnal Akuntansi Universitas Udayana, 17(2).Enders, W. (2004). Applied Econometric Time Series. John Wiley & Sons.Fama, E. F. (1970). Efficient Capital Markets: A Review of Theory and Empirical Work. The Journal of Finance, 25(2), 383-417.Fontanills, G. A., & Gentile, T. (2003). The Volatility Course. Hoboken: John Wiley & sons, Inc.Gallant, R. A., Rossi, P. E., & Tauchen, G. (1992). Stock Prices and Volume. The Review of financial Studies, 5(2).Ginting, M. R., Topowijono, & Sulasmiyati, S. (2016). Pengaruh Tingkat Suku Bunga, Nilai Tukar dan Inflasi terhadap Harga Saham (Studi Pada Sub-Sektor Perbankan di Bursa Efek Indonesia Periode 2011-2015). Jurnal Administrasi Bisnis (JAB), 35(2).Girard, E., & Omran, M. (2009). On the Relationship between Trading Volume and Stock Price Volatility in CASE. Intenational Journal of Managerial Finance, 5(1), 110-134.Griffiths, W. E., Hill, R. C., & Lim, G. C. (2008). Using Eviews for Principles of Econometrics Third Edition. New Jersey: John Wiley & Sons.Heryanto. (2010). Analisis Inflasi. BI Rate, Infalsi, Kurs Rupiah dan Jumalh Uang Beredar, Terhadap Volume Perdagangan Saham di Bursa Efek Indonesia (Unpublised Thesis), Universitas Islam Negeri Syarif Hidayatullah, Indonesia.Huang, R. D., & Masulis, R. W. (2002). Trading Activity and Stock Price Volatility: Evidence from the London Stock Exchange. Journal of Emprical Finance.Hugida, L. (2011). Analisis Faktor-faktor yang Mempengaruhi Volatilitas Harga Saham (Studi Pada Perusahaan yang Terdaftar dalam Indeks LQ45 periode 2006-2009) (Unpublised Thesis), Universitas Diponegoro, Indonesia.Hussainey, K., Mgbame, C. O., & Chijoke-Mgbame, A. M. (2011). Dividend Policy and Share Price Volatility: UK Evidence. Journal of Risk Finance, 12(1).Hyde, K. (2000). Recognising Deductive Processes in Qualitative Research. Qualitative Market Research: An International Journal, 3, 82-89.Jawaid, S. T., & Ul Haq, A. (2012). Effects of Interest Rate, Exchange Rate, and Their Volatilities on Stock Prices: Evidence from Banking Industry of Pakistan. Theoritical and Applied Economics, 155-166.Jonathan, T. I. (2013). Analisa Pengaruh Inflasi, Suku Bunga dan Kurs Terhadap Volume Transaksi Pada Indeks LQ45. FINESTA, Vol.1, No.2.Kamuti, H. M. (2013). The Dynamic Relationship Between Stock Price Volatility and Trading Volume at the Nairobi Securities Exchange, Research Project, University of Nairobi.Karpoff, J. M. (1986). A Theory of Trading Volume. The Journal of Finance, 41(5).Khurniaji, A. W., & Raharja, S. (2013). Hubungan Kebijakan Dividen (Deividen Payout Ratio dan Dividend Yield) terhadap Volatilitas Harga Saham Perusahaan-perusahaan yang Terdaftar di Bursa Efek Indonesia. Diponegoro Journal of Accounting, 2(3).Kirui, E., Wawire, N. H., & Onono, P. O. (2014). Macroeconomic Variables, Volatility and Stock Market Returns: A Case of Nairobi Securities Exchange, Kenya. International Journal of Economics and Finance, 6(8).Kothari, C. R. (2004). Research Methodology Methods and Techniques. New Delhi: New Age International (P) Ltd.Lucey, B. M. (2005). Does Volume Provide Infromation? Evidence from the Irish Stock Market. Applied Financial Economic Letters, 1(2).Malkiel, B. G. (2003). The Efficient Market Hypothesis and Its Critics. Journal of Economic Perspectives, 17(1), 59-82.Malliaris, A. G., & Urrutia, J. L. (1998). Volume and Price Relationships: Hypothesis and Testing for Africultural Futures. The Journal of Futures markets, 18(1), 53-72.Mankiw, N. G. (2004). Priciples of Macroeconomics (Vol. Third Edition). Thomson South Western.Marczyk, G., DeMatteo, D., & Festinger, D. (2005). Essential of Research Design and Methodology. Hoboken: John Wiley &Sons, Inc.Muibi, S. O., Osi, A. R., Evans, O., & Seun, T. (2016). Determinants of Stock Trading volume in Nigeria: Money Demand Approach. Journal of Empirical Economics, 5(2), 74-89.Muktadir-al-Mukit, D. (2012). Effects of Interest Rate and Exchange Rate on Volatility of Market Index at Dhaka Stock Exchange. VII(2).Mumo, M. P. (2017). Effects of Macroeconomic Volatility on Stock Prices in Kenya: A Cointegration Evidence from the Nairobi Securities Exchange (NSE). International Journal of Economics and Finance, 9(2).Nasir, J. L., Diana, N., & Mawardi, M. C. (2018). Analisis Faktor-Faktor yang Mempengaruhi Volatilitas Harga Saham. E-JRA, 7(9).Newbold, P., Carlson, W. L., & Throne, B. M. (2003). Statistics for Business and Economics. Pearson Education, 5.Nugroho, H. (2008). Analisis Pengaruh Inflasi, Suku Bunga, Kurs dan Jumlah Uang Beredar Terhadap Indeks LQ45 (Studi Kasus Pada BEI Periode 2002-2007) (Unpublished Thesis), Universitas Diponegoro, Indonesia.Omorokunwa, O. G., & Ikponmwosa, N. (2014). Macroeconomics Variables and Stock Price Volatility in Nigeria. Annals of the University of Petrosani, Economics, 14(1), 259-268.Omotunde, R. A., Nwaogwugwu, I., & Nwokoma, N. I. (2016). Interest Rate Shocks and Stock Market Volatility in Nigeria. West African Journal of Monetary and Economic Integration, 16(2).Oseni, I. O., & Nwosa, P. I. (2011). Stock Market Volatility and Macroeconomic Variables Volatility in Nigeria: An Exponential GARCH Approach. Journal of Economics ad Sustainable Development, 2(10).Osisanwo, B. G., & Atanda, A. A. (2012). Determinant of stock market returns in Nigeria: A Time Series Analysis. African Journal of Scientific Research, 9(1).Pramaditya , R. (2008). Pengaruh SBI, Nilai Kurs AS (USD) dan Inflasi Terhadap Volume Perdagangan Saham Perbankan yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2004-2006 (Unpublished Thesis), Universitas Mercu Buana, Indonesia.Pratama, M. A. (2011). Analisis Pengaruh Suku Bunga dan Nilai Tukar Terhadap Volatilitas dan Return Pada Indeks Saham Sektoral di Bursa Efek Indonesia, Institut Pertanian Bogor, Indonesia.Prempeh, K. B. (2016). Macroeconomic Variables and Stock Price Volatility in Ghana. MPRA Paper No. 70545.Rahardjo, S. (2006). Kiat Membangun Aset Kekayaan. Jakarta: Elex Media Komputindo.Reilly, F. K., & Brown, K. C. (2003). Investment Analysis & Portfolio Management (Vol. Seventh Edition). USA: South western-Thomson.Retherford, R. D., & Choe, M. K. (1993). Statistical Model for Causal Analysis. New York: John Wiley &Sons, Inc.Romli, H., Wulandari, M. F., & Pratiwi, T. S. (2017). Faktor-faktor yang Mempengaruhi Volatilitas Harga Saham pada PT Waskita Karya Tbk. Jurnal Ilmiah Ekonomi Global Masa Kini, 8(1).Ross, S. A. (1976). The Arbitrage Theory of Capital Asset pricing. Journal of Economic Theory, 13, 341-360.Saatcionglu, K., & Starks, L. (1998). The Stock Price-volume Relationship in Emerging Stock Markets: The Case of Latin America. International Journal of Forecasting 14, 215-225.Sahu, T. N. (2015). Macroeconomic Variables and Security Price in India during the Liberalized Period. New York: Palgrave Macmillan.Samsul, M. (2006). Pasar Modal dan Manajemen Portofolio. Erlangga.Saunders, M., Lewis, P., & Thornhill, A. (2009). Research Methods for Business Students (Vol. 5). England: Pearson Education.Schwert, G. W. (1989). Why Does Stock Market Volatility Changes Over Time? The Journal of Finance, XLIV, No. 5.Sihombing, L. I. (2009). Pengaruh Inflasi, Kurs, Investasi dan Suku Bunga Sertifikat Bank Indonesia (SBI) terhadap Harga Saham dan Volume Perdagangan Saham PT. Bank Rakyat Indonesia (Tbk) di Bursa Efek Indonesia (Unpublished Thesis), Universitas Sumatera Utara, Indonesia.Singh, Y. K. (2006). Fundamental of Research Methodology and Statictics. New Delhi: New Age international (P) Ltd.Spiro, P. S. (1990). The Impact of Interest Rate Chnage on Stock Price Volatility. The Journal of Portfolio Management.Suniarti, L. (2019). Analisis Faktor Fundamental yang Mempengaruhi Volatilitas Harga Saham (Study Pada Perusahaan yang Terdaftar Dalam Inde LQ45 Periode Tahun 2008-2017). 7(1).Sutrisno, B. (2017). Hubungan Volatilitas dan Volume Perdagangan di Bursa Efek Indonesia. Jurnal Bisnis dan Manajemen, 7(1), 15-26.Tandelilin, E. (2010). Portofolio dan Investasi Teori dan Aplikasi. Yogyakarta: Kanisius.Taslim, A., & Wijayanto, A. (2016). Pengaruh Frekuensi Perdagangan Saham, Volume Perdagangan Saham, Kapitalisasi Pasar dan Jumlah Hari Perdagangan Terhadap Return Saham. Management Analysis Journal, 5(1).Tserkezos, E. (2009). Temporal Aggragation and Ramsey's (RESET) Test for Functional Form: results from Monet Carlo Experiment. Conference paper, 1-12.Vogelvang, B. (2005). Econometrics Theory and Applications with Eviews. England: Pearson Education Limited.Walter, E. (1995). Applied Econometric Time Series. Canada: Jhon Wiley & Sons, Inc.Widarjono, A. (2005). Ekonometrika: Teori dan Aplikasi untuk Ekonomi dan Bisnis. Yogyakarta: Ekonisia.Widoatmodjo, S. (2015). Seri Akademis Pengetahuan Pasar Modal untuk Konteks Indonesia. Jakarta: Elex Media Komputindo.Wira, V. (2012). Pengaruh Kinerja Perusahaan Terhadap Likuiditas Saham Menggunakan Trading TurnOver (Studi Kasus Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia). Jurnal Manajemen dan Kewirausahaan, 3, No. 2.Yuliana, F., Wijaya, E. Y., & Haryetti. (2014). Analisa pengaruh Tingkat Suku Bunga, Inflasi, Kurs, dan Jumlah Uang Beredar terhadap Volume Perdagangan Saham. JOM FEKON, 1(2).Zan, S., & Wei, C. (2003). The Macroeconomic Determinants of Stock Price Volatility: Evidence from Taiwan, South Korea, Singapore and Hong Kong. Environmental and Management Research, 8(2).Â Â